The Impact of Student-Centered Approach on Kurdish EFL University Students’ Speaking Skills - Shakar Salah Rahim; Twana Saadi Hamid (Zanco Journal of Human Sciences, 2026)
This study investigates the impact of a student-centered approach (SCA) on Kurdish EFL university students’ academic speaking skills. This topic is significant because there are theoretical and empirical gaps in the existing literature. While prior research in the Kurdistan Region of Iraq (KRI) has focused on general English (EGP), little has addressed English for Academic Purposes (EAP) and academic speaking skills in particular. In fact, no studies have provided a practical and replicable step by step SCA framework. Furthermore, existing research has failed to accurately and systematically measure both objective performance through tests and subjective learner perceptions through questionnaires. Using a quantitative research design, this study employed a 12-week intervention with 45 students from the University of Sulaimani, College of Dentistry, Department of Basic Sciences, split into an experimental group (SCA) and a control group (TCA). The findings show that the SCA was more effective numerically than the traditional TCA across all measured components. But the fluency and coherence component was the only component with a statistically significant improvement in the experimental group compared to the control group. This study fills a critical gap by providing a tailored, five-step SCA model to give teachers clearly defined classroom practices. This work also reveals a warning: while the SCA is highly effective, it may foster overestimation or overconfidence without actual competence. Ultimately, this paper provides an evidence-based pedagogical background for enhancing academic speaking proficiency in the KRI context.